Pilot application of biofeedback training program for racket sports players - Park, S.-H.; Hwang, S.; Lee, S.-M. (Annals of Applied Sport Science, 2021)
Background: A biofeedback program receives attention as an intervention program for athletes to regulate their psychological state. Objectives. The purpose was to apply for a heart rate variability (HRV) biofeedback training program and validate its effectiveness for racket sports players. Methods: The participants were eight elite sport athletes (three men and five women): five squash players and three tennis players. The HRV biofeedback training program consisted of ten sessions in which the participants performed paced breathing for 10 minutes (e.g., 5-second inspiration and 5-second expiration). The means and standard deviations of the collected data were calculated, and the Wilcoxon signed-rank test was performed using SPSS windows 18.0. Results: Changes in HRV by the biofeedback training were significant. Standard Deviation of Normal to Normal (SDNN; Z = -2.38, p = 0.017) in time domain and Low Frequency (LF, Z = -2.52, p = 0.12) and the ratio of LF to High Frequency (HF; Z = -2.52, p = 0.12) in frequency domain were increased. Conclusion: The present study provides empirical results needed to expand HRV biofeedback training research for the performance enhancement program of athletes.